2002
DOI: 10.1136/thorax.57.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis among political asylum seekers screened at Heathrow Airport, London, 1995-9

Abstract: Background: Over 50% of cases of tuberculosis (TB) in the UK occur in people born overseas, and new entrants to the country are screened for TB. A study was undertaken to determine the prevalence and disease characteristics of pulmonary TB in new entrants to the UK seeking political asylum. Methods: A retrospective analysis of the results of screening 53 911 political asylum seekers arriving at Heathrow Airport between 1995 and 1999 was performed by studying Airport Health Control Unit records and hospital med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 4 publications
2
26
0
1
Order By: Relevance
“…The PTB point prevalence on arrival in the present study was 270 per 100,000 immigrants, which is lower than documented among asylum seekers at Heathrow Airport, London, UK [13] and in Belgium [14], but is higher than in Somalis screened in Norway [15] or in Switzerland [16] (415, 252, 248 and 198 cases per 100,000 immigrants, respectively). The gap in TB prevalence between Ethiopia and Somalia may be related to the relatively higher TB prevalence in Ethiopia, the age composition and the basic health status of the immigrants to Israel, and the active case-finding process applied to all immigrants.…”
Section: Resultsmentioning
confidence: 49%
“…The PTB point prevalence on arrival in the present study was 270 per 100,000 immigrants, which is lower than documented among asylum seekers at Heathrow Airport, London, UK [13] and in Belgium [14], but is higher than in Somalis screened in Norway [15] or in Switzerland [16] (415, 252, 248 and 198 cases per 100,000 immigrants, respectively). The gap in TB prevalence between Ethiopia and Somalia may be related to the relatively higher TB prevalence in Ethiopia, the age composition and the basic health status of the immigrants to Israel, and the active case-finding process applied to all immigrants.…”
Section: Resultsmentioning
confidence: 49%
“…12 studies reported information about the geographic origin of the migrants [19-21, 26-31, 36, 38, 39], while only three studies reported a sex distribution of pulmonary tuberculosis cases [22,29,31]. Among the studies reporting the geographic origin of immigrants, six reported cases from Europe (median (interquartile range) number of cases: 10 (4-8); median number of immigrants: 2,950 (945-8,462)) [19-21, 26, 28, 29], six reported cases from Asia (median number of cases: 24 (13-71); median number of immigrants: 2,089 (1,863-9,328)) [20,27,30,31,36,38], three reported cases from Africa (median number of cases: 14 ; median number of immigrants: 1,732 (1,390-10,490)) [19][20][21], one reported cases from the Middle East [20] and, finally, one paper reported cases from Haiti [39]. Table 1 summarises the findings of the 22 studies that reported cases of active pulmonary tuberculosis among migrants and the prevalence of tuberculosis among the general population in the host countries.…”
Section: Resultsmentioning
confidence: 99%
“…The median (interquartile range) number of cases of pulmonary tuberculosis among immigrants was 31 , while the median number of immigrants screened in each study was 6,526 (945-19,912). Of the 22 studies, seven reported pulmonary tuberculosis cases among refugees [26][27][28][29][30][31]38], seven reported cases among regular immigrants [32][33][34][35][36][37]39], seven reported cases among asylum seekers [18][19][20][21][22][23][24] and one did not report any pulmonary tuberculosis case [25]. 12 studies reported information about the geographic origin of the migrants [19-21, 26-31, 36, 38, 39], while only three studies reported a sex distribution of pulmonary tuberculosis cases [22,29,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TB screening of other categories of immigrants could also be improved. These problems are not unique to Norway but are also experienced in other countries (2,8).…”
mentioning
confidence: 98%